PERAN KOMUNIKASI DAN POLA ASUH ORANGTUA TERHADAP PERILAKU SEKSUAL SISWA SEKOLAH MENENGAH PERTAMA DI KECAMATAN SUKORAMBI KABUPATEN JEMBER - Holfi Mariyatul Kiptiyah; Ni'mal Baroya (Universitas Jember, 2019)
Problem high-risk sexual behavior that teens when dating is the responbility of everyone, especially parents.. The parental presence of effective communication and appropriate parenting pattern is expected to cope with the increasing high-risk sexual behavior in adolescents. This study attempts to analyze the parental presence by sexual behavior risky on student dating in SMPN Sukorambi Jember Regency. The research is the study analytic by design cross-sectional. 101 students of SMP Sukorambi who claimed to have/was in the dating. The results showed that characteristics of respondents there are two variables related to sexual behavior during dating ie sex and age variable. The variable of parental presence both has a significant relationship with the sexual behavior of parent's communication and parenting. Teen's sexual behavior, when dating is classified as high-risk behavior, is mutually attached to the genitals with limited clothing. From this study, it was concluded that the parental presence through effective communication and discussing about sexuality and educating with autoritative parenting can prevent adolescents from high-risk sexual behavior when dating.